Modeling the causal dynamics among energy consumption, economic growth, and oil import prices: A panel co-integration analysis for EU economies - Gibba, Alieu; Khan, Muhammad Kamran (Frontiers in Environmental Economics, 2023)
The circular economy creates a robust system that can combat global concerns like climate change, biodiversity loss, waste, and pollution by decoupling economic activity from the use of natural resources. This study for the first time in European Union (EU) countries, examines the impact of economic growth, urbanization, investment in information technology and communication (IT&C), oil import prices, environmental technology and environmental tax on energy consumption. Additionally, it also examined the impact of oil import prices, urbanization, energy consumption, investment in information technology and communication, environmental technology and environmental tax on economic growth by using panel autoregressive distributed lag (ARDL) model for the estimations over the period 1990–2020. According to the correlation matrix's estimations, findings suggest that the economic expansion of the EU member countries is positively influenced by oil import prices, urbanization, environmental technology and energy consumption, while negatively impacted by investment in IT&C and environmental taxes both in the short and long-run. On the other hand, energy consumption is found to be positively impacted by economic growth, urbanization and oil import prices while negatively influenced by investment in IT&C, environmental taxes and environmental related technologies. In addition, the results of the panel ARDL model indicate that oil import prices positively and significantly influence the economic growth of the EU members. However, results of urbanization reveal a negative influence on economic growth in the short-term, but in the long-run, it has a favorable and considerable influence on the economic growth of the European Union. Finally, the research has implications for policy makers and regulators in the EU.